Toni Morrison A Literary Life - Wagner-Martin, L. (Literary Lives, 2015)
A reading of the oeuvre of Toni Morrison — fiction, non-fiction, and other — drawing extensively from her many interviews as well as her primary texts. The author aligns Morrison's novels with the works of Virginia Woolf and William Faulkner, assessing her works as among the most innovative, and most significant, worldwide, of the past fifty years.